New functional aspects of the L-arginine-nitric oxide metabolism within the circulating blood - Kleinbongard, Petra; Keymel, Stefanie; Kelm, Malte (Thrombosis and Haemostasis, 2007)
Nitric oxide (NO) is a signaling molecule of major importance modulating not only the function of the vascular wall but also that of blood cells, such as platelets and leukocytes. The synthesis of NO in the circulation has been attributed mainly to the vascular endothelium. Red blood cells (RBC) have been demonstrated to carry a non-functional NOS and – due to their huge haemoglobin content – have been assumed to metabolize large quantities of NO. More recently, however, RBC have been identified to reversibly bind, transport, and release NO within the cardiovascular system. We provide evidence that RBC from humans express an active and functional endothelial type NOS. RBC NOS activity may regulate deformability of RBC, and inhibits activation of platelets. This review aims to discuss the potential role of RBC NOS in the circulation and new concepts of NO research in the microcirculation.
Keywords: Red blood cells; nitric oxide; cell function